A novel approach of mapping landscape aesthetic value and its validation with rural tourism data - Lontai-SzilágyiZsuzsanna; Bertalan-BalázsBoglárka; Zsiros, Bernadett; Vasvári, Mária; KumarSingh Sudhir; Nilanchal, Patel; Martonné ErdősKatalin; Szabó, Szilárd (Hungarian Geographical Bulletin, 2019)
Landscape aesthetic research that emerged from the second half of the 20th century has become increasingly appreciated and popular in the last few decades. There are two main reasons for this. On the one hand, it was recognized the role of landscape aesthetics in land use and environmental planning, management and conservation. On the other hand, its definition among Cultural Ecosystem Services has made it clear that landscape aesthetics has significant impact on human well-being and there is a need to examine it in the concept of Ecosystem Services and, in particular, Cultural Ecosystem Services (CES). The mapping of landscape aesthetics is mostly based on the exclusive evaluation of objective, biophysical landscape factors. The aim of the research was to create the landscape aesthetic map of Hungary with a novel method based on human perception. For this, a questionnaire survey and a GIS approach were used. In order to better understand the role of factors influencing the aesthetic value of the landscape, value maps separately for land cover and elevation that are decisive for the landscape experience were prepared. To validate the results of the maps, and contribute a better understanding of the interrelationship between CES, a certain tourism product was chosen, and the connection between landscape aesthetics and the offer of rural tourism was examined in Hungary and in the Danube Bend priority tourism development area. Our findings show that there is a difference in the results of the objective (GIS-based) and subjective (questionnaire-based) assessment of landscape aesthetic value with the more important role of elevation in the latter. According to our tourism product-based analysis, which represents a niche approach in its kind, landscape values are higher in the areas with rural accommodation. At the same time, based on the results of the Danube Bend region, it can also be concluded that elevation and land cover together are crucial factors in landscapes considered to be the most valuable in aesthetic terms. The most direct practical application of our research is to orientate further tourism development of the new Danube Bend area designated in 2017.